Burnout Syndrome among Healthcare Workers in Lithuania as a Former Soviet Country - Aušra Deksnytė; Ramūnas Aranauskas; Vytautas Kasiulevičius; Lukas Aranauskas; Alvydas Navickas; Rugilė Jurkytė; Karolina Palinauskaitė; Diana Zlotnikovienė (Neurologijos seminarai)
Objective. Measure the prevalence of burnout syndrome (BOS) among the healthcare workers (HCW) in Lithuania and the factors influencing it.